Qing-Luo-Yin Eased Adjuvant-Induced Arthritis by Inhibiting SIRT1-Controlled Visfatin Production in White Adipose Tissues - Wang DD; Song MK; Yin Q; Chen WG; Olatunji OJ; Yang K; Zuo J (Dove Medical Press, 2024)
Dan-Dan Wang,1,2,* Meng-Ke Song,1,3,* Qin Yin,1,2 Wen-Gang Chen,2 Opeyemi Joshua Olatunji,4 Kui Yang,3 Jian Zuo1,3,5 1Xin'an Medicine Research Center, The First Affiliated Hospital of Wannan Medical College (Yijishan Hospital), Wuhu, 241000, People's Republic of China; 2Department of Pharmacy, the Second Affiliated Hospital of Wannan Medical College, Wuhu, 241000, People's Republic of China; 3Research Center of Integration of Traditional Chinese and Western Medicine, Wannan Medical College, Wuhu, 241000, People's Republic of China; 4African Genome Center, Mohammed VI Polytechnic University, Ben Guerir, 43150, Morocco; 5Anhui Province Key Laboratory of Non-Coding RNA Basic and Clinical Transformation, Wannan Medical College, Wuhu, 241000, People's Republic of China*These authors contributed equally to this workCorrespondence: Kui Yang; Jian Zuo, Email ykui15556689670@163.com; zuojian8178@163.comBackground: Nicotinamide adenine dinucleotide (NAD)-dependent deacetylase SIRT1 regulates both metabolism and immune functions. This study investigated if SIRT1 inhibitory property of herbal formula Qing-Luo-Yin (QLY) contributed to its anti-rheumatic effects.Methods: Adjuvant-induced arthritis (AIA) rats were treated by QLY and nicotinamide mononucleotide (NMN, a biosynthesis precursor of NAD) for 38 days. After sacrifice, blood, paws, liver and white adipose tissues (WAT) were collected. Pre-adipocytes were cultured by the rats' serum. The medium was used for monocytes culture. Some pre-adipocytes were treated by QLY-derived SIRT1 inhibitors. SIRT1 was silenced or overexpressed beforehand. The samples were subjected to kits-based quantification, polymerase-chain reaction, western-blot, immunofluorescence, and histology experiments.Results: AIA rats experienced significant fat loss in liver and WAT. Expression of many SIRT1-related signals like PPARγ, PGC-1α, HSL, ATGL and CPT-1A were altered. QLY attenuated all these abnormalities and joint injuries. By pan-acetylation up-regulation, visfatin was obviously reduced in QLY-treated AIA rats' blood (from 191.8 to 127.0 pg/mL). NMN sustained SIRT1 activation by replenishing NAD, and weakened these effects. QLY-containing serum and the related compounds showed similar impacts on pre-adipocytes, resembling the changes in QLY-treated AIA rats' WAT. These treatments suppressed AIA serum-induced visfatin secretion (from 49.3 to 36.1 and 30.7 pg/mL). This effect was impaired by SIRT1 overexpression. The medium from the compounds-treated pre-adipocytes impaired NF-κB activation in AIA serum-cultured monocytes.Conclusion: Besides fat depletion, SIRT1 up-regulation in rheumatic subjects' WAT promotes visfatin production, and exacerbates inflammation. SIRT1 inhibition in WAT is an anti-rheumatic way of QLY independent of immune regulation.Keywords: visfatin, PPARγ, rheumatoid arthritis, Traditional Chinese Medicine, adipocyte